Upaya Pengembangan Usaha Bumdes di Desa Kadubereum: Strategi Jitu Apa Yang Harus Dilakukan? - Rahmawati, Rahmawati; Yusuf, Maulana; Satrio, Agung (ANTASENA: Governance and Innovation Journal, 2024)
One of the mandatories of Law No. 6/2014 on Villages is the obligation to establish a Village-Owned Enterprise or Bumdesa. Village owned enterprise (VOE) is the motor of economic mobilisation in the village as stated in Article 5. Kadubereum Village in Serang Regency is a village with agricultural and plantation potential. Based on the potential of the village, VOE Sejahtera was formed with superior products from the plantation, namely purple sweet potatoes. However, in its development, there are obstacles related to marketing, raw materials and also the budget in the business development of VOE Sejahtera. This research aims to analysis what strategies can be done to develop VOE Sejahtera business. The method used is qualitative with a case study approach. Data collection through FGDs on VOE management, village officials and community leaders. The results showed that from environmental observations, the formation of BUMDes Sejahtera aims to utilise the community's plantation products in the form of purple sweet potatoes which often experience low selling prices when the harvest arrives. The strategy developed was to make purple sweet potato chips covered in chocolate and labelled UCOK. Unfortunately, the marketing of UCOK products is still in the local market even though it has entered minimarkets or retailers in Serang Regency. The Office of Cooperatives and MSMEs of Serang Regency has provided training to the VOE management in the form of packaging and registering a certificate from BPOM Serang